Supporting smart citizens: Design templates for co-designing data-intensive technologies. (June 2020) - Wolff, Annika; Barker, Matthew; Hudson, Lorraine; Seffah, Ahmed
Abstract: The design of interactive technologies for smart cities requires understanding the interactions between diverse data, physical objects, existing services and different stakeholders. Yet there is a lack of supporting methods and tools for modelling the complex interaction processes, especially between humans and data. This can inhibit engagement with smart city applications and services design, particularly for those who are not experts in developing smart technologies. This paper describes the development of a typology and a set of design templates, derived from analysis of both existing and proposed examples of smart apps and services. In the process, it highlights the capability of citizens to contribute to smart city design, if given appropriate support as part of a co-design process. In this regard, we contribute a common language for both professional and non-professional designers to discuss how smart city technologies turn data into services. Highlights: Citizens show good capabilities for ideating new smart technologies. Citizens need support to join the debate on an equal footing to smart city professionals. Design templates help citizens to more easily contribute to smart city design.